When Compact Sets are α-Closed - Ali, Haider Jebur; Dahham, Marwa Makki (Al-Nahrain Journal of Science, 2018)
This paper is devoted to introduce new concepts so called K( c)-spaces several various theorems about these concepts are provided in addition, further properties are studied such as the relationships between those concepts and other types of K( c)-spaces are investigated.